Analisis Pengaruh Perlakuan Microwave Plasma dalam Cairan Terhadap Kadar Glukosa dan Produk Nano Material Pada Ampas Tebu - Muh Firdan Nurdin; Andi Erwin Eka Putra; Novriany Amaliyah; Mukhtar Rahman; Andi Mangkau (Jurnal Teknik Mesin Sinergi, 2021)
Sugarcane (Saccharum officinarum L.) is a raw material that is processed to produce crystal sugar and bioethanol. The process produces sugarcane bagasse. In this study, The liquid-plasma treatment based on microwave plasma in the liquid was used to treat sugarcane bagasse to observe the effect on glucose concentration and gain byproducts. The energy input parameters were varied by 340, 360, and 400 W with irradiation time variations of 1, 3, and 5 minutes. Nelson Somogyi's method was used to determine the percentage of glucose as well as Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscope (SEM), and Image-J software to characterize the side-product of the samples. The results showed that the glucose concentration reduced around 27.6% - 99.2 % after microwave plasma in-liquid treatment at the energy input of 340 Watt and 360 Watt, respectively, with an irradiation time of 5 minutes. The side-product is cellulose nanoparticles which have an average diameter of 92, 106, and 169 nm